Laboratory fish in biomedical research : biology, husbandry and research applications for zebrafish, medaka, killifish, swordtail fish, cavefish, stickleback, goldfish and Danionella translucida - D'Angelo, Livia; De Girolamo, Paolo (Academic Press, an imprint of Elsevier, 2022)
"Fish, particularly zebrafish, have become the fatest-growing segment of the research population. They offer several advantages in biology and applicable technologies and thus are employed in numerous research fields. Laboratory Fish in Biomedical Research: Biology, Husbandry and Research Applications for Zebrafish, Medaka, Killifish, Cavefish, Stickleback, Goldfish and Danionella translucida addresses the relevant, increasing need to collect cutting-edge knowledge on the most common freshwater species in terms of husbandry, maintenance, welfare, and experimental protocols under standard laboratory conditions. Key features: provides husbandry and management protocols, devices, and water systems; discusses strengths and weaknesses of breeding; explores potential scientific applications and experimental protocols of freshwater fish used the most in scientific endeavors"--Publisher's description.